Navigating social capital development through organisational citizenship behaviour in local government bureaucracy - Bambang Utoyo Sutiyoso; Dodi Faedlulloh (Cogent Social Sciences, 2024)
Weber’s bureaucratic paradigm and the application of scientific management have led to organizational structures that prioritize efficiency over the human dimension. This has resulted in hierarchical human interactions, rigidity, and diminished motivation and productivity, particularly in the public sector. Social capital and organizational citizenship behavior (OCB) are essential for organizational success. Social capital refers to the networks and relationships that facilitate cooperation and trust. OCB is discretionary behavior that goes beyond job requirements. This study examines the impact of social capital and OCB on civil servant performance in bureaucratic settings. The study was conducted in two research sites, Central Lampung Regency and Metro City were chosen due to regional expansion considerations. Empirical data was collected through questionnaires and analyzed using the Analytical Hierarchy Process (AHP). The findings reveal that social capital and OCB have a significant impact on civil servant performance. In Central Lampung Regency, the civic virtue dimension of social capital and the altruism dimension of OCB were the most important factors. In Metro City, the trust dimension of social capital was the most important factor. This study synthesizes social capital and OCB perspectives within organizational theory. Furthermore, this research emphasizes integrating socio-psychological factors alongside structural considerations in organizational analyses.